Madurella mycetomatis grains within a eumycetoma lesion are clonal. (14th July 2022) - Nyuykonge, Bertrand; Siddig, Emmanuel Edwar; Konings, Mickey; Bakhiet, Sahar; Verbon, Annelies; Klaassen, Corné H W; Fahal, Ahmed Hassan; van de Sande, Wendy W J
Abstract: Eumycetoma is a neglected tropical infection of the subcutaneous tissue, characterized by tumor-like lesions and most commonly caused by the fungus Madurella mycetomatis . In the tissue, M. mycetomatis organizes itself in grains, and within a single lesion, thousands of grains can be present. The current hypothesis is that all these grains originate from a single causative agent, however, this hypothesis was never proven. Here, we used our recently developed Mmy STR assay, a highly discriminative typing method, to determine the genotypes of multiple grains within a single lesion. Multiple grains from surgical lesions obtained from 11 patients were isolated and genotyped using the Mmy STR panel. Within a single lesion, all tested grains shared the same genotype. Only in one single grain from one patient, a difference of one repeat unit in one Mmy STR marker was noted relative to the other grains from that patient. We conclude that within these lesions the grains originate from a single clone and that the inherent unstable nature of the microsatellite markers may lead to small genotypic differences. Lay Abstract: In lesions of the implantation mycosis mycetoma many Madurella mycetomatis grains are noted. It was unknown if grains arose after implantation of a single isolate or a mixture of genetically diverse isolates. By typing the mycetoma grains we showed that all grains within a single lesion were clonal and originated from a single isolate.